Characterization of dehydrated keratin protein extracted from chicken feather - Alashwal, B Y; Gupta, Arun; Husain, M S B (IOP Publishing, 2019)
Keratin is one of the most important biomaterials due to its relatively good biocompatibility, high physicochemical with excellent mechanical properties and good film coordination ability. Chicken feathers are a major waste in poultry industries however, 90% of pure keratin can be obtained from the total featherweight. Chicken feathers are abundant of keratin protein which can be considered as a suitable protein source and used as a component in the cosmetic and pharmaceutical industry. The aim of this study is to extract keratin protein from chicken feather source. The chemical structure of the keratin protein was examined by Fourier transform infrared pectroscopy (FTIR). The results showed the presence of, Amide I-III bands, which gave critical information on the protein conformation and alteration in backbone structure of the keratin., Surface morphology analysis was described by Scanning electron microscopy (SEM). The extracted keratin was found to present aspheric shaped, small microspheres with smooth surface. Meanwhile the X-Ray Diffraction results showed the crystalline form of the chicken feather dehydrated keratin. The diffraction peak was indexed for the β-sheet crystalline structure of keratin. In conclusion, the characterization of keratin extracted from chicken feathers was successfully performed using the above mentioned analyses.